Book reviews - Jacqueline Reid-Walsh; Tom Ue; Michael Wilson; Michael Levy (2018)
Book ReviewsWhen We Were Alone, David A. Robertson and Julie Flett (2016) Winnipeg, Manitoba: Highwater Press, 24 pp., ISBN: 978-1-55379-673-2, h/bk, £14.25.Frankenstein or, The Modern Prometheus: The 200th Anniversary Edition, Mary Shelley (author) and David Plunkert (illus.) (2018) Beverly: Rockport Publishers-The Quarto Group, 248 pp., ISBN 978-1-63159-397-0, h/bk, $25.00Party Pieces: Oral Storytelling and Social Performance in Joyce and Beckett, Alan W. Friedman (2007) New York: Syracuse University Press, 256 pp., ISBN 978-0-81563-123-1, h/bk, £43.95Journeys from the Abyss: The Holocaust and Forced Migration from the 1880s to the Present, Tony Kushner (2016) Liverpool: Liverpool University Press, 360 pp., ISBN: 978-1-78694-062-9, h/bk, £85.00, p/bk, £24.95, ebook £24.95